2018
DOI: 10.3390/molecules23010146
|View full text |Cite
|
Sign up to set email alerts
|

α-Glucosidase Inhibition and Antibacterial Activity of Secondary Metabolites from the Ecuadorian Species Clinopodium taxifolium (Kunth) Govaerts

Abstract: The phytochemical investigation of both volatile and fixed metabolites of Clinopodium taxifolium (Kunth) Govaerts (Lamiaceae) was performed for the first time. It allowed the isolation and characterization of the essential oil and six known compounds: carvacrol (1), squalane (2), uvaol (3), erythrodiol (4), ursolic acid (5), and salvigenin (6). Their structures were identified and characterized by Nuclear Magnetic Resonance (NMR) and Gas Chromatography coupled to Mass Spectroscopy (GC-MS), and corroborated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 43 publications
(30 reference statements)
1
13
0
Order By: Relevance
“…As part of a project aiming to valorize Ecuadorian spontaneous flora [8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25], the chemical composition and sensory profile of Myrcianthes myrsinoides (Kunth) Grifo and Myrcia mollis (Kunth) DC essential oils (EOs) are here reported for the first time. Gas chromatography mass spectrometry (GC-MS) and enantioselective GC-MS were used for the quali-quantitative analysis, and GC-olfactometry (GC-O) to evaluate the odor active compounds.…”
Section: Introductionmentioning
confidence: 99%
“…As part of a project aiming to valorize Ecuadorian spontaneous flora [8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25], the chemical composition and sensory profile of Myrcianthes myrsinoides (Kunth) Grifo and Myrcia mollis (Kunth) DC essential oils (EOs) are here reported for the first time. Gas chromatography mass spectrometry (GC-MS) and enantioselective GC-MS were used for the quali-quantitative analysis, and GC-olfactometry (GC-O) to evaluate the odor active compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the bioactive fractions were realized and subjected to chromatographic techniques to isolate the active compounds which were characterized by spectroscopic and spectrometric techniques [one‐dimensional (1D) nuclear magnetic resonance (NMR), two‐dimensional (2D) NMR, and high‐resolution electrospray ionization mass spectrometry (HR‐ESI‐MS)]. Out of the active fractions, six compounds; squalene, ursolic acid {[α] 22 D + 91.3 ( c 0.1, CHCl 3 )}, betulonic acid {[α] 22 D + 47.5 ( c 0.1, CHCl 3 )}, cabraleone {[α] 22 D + 73.7 ( c 0.1, CHCl 3 )}, ursolic acid acetate {[α] 22 D + 87.9 ( c 0.1, CHCl 3 )}, and 27‐ p‐E ‐coumaroyloxyursolic acid {[α] 22 D + 7.4 ( c 0.1, CHCl 3 )} . Chemical structures of these compounds are given in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…reported that about 50% of all the phytochemical publications on the Ecuadorian flora referred only to 8 of the 245 botanical families of the native species known in the country [ 2 ]. For this reason, the authors have been involved for years in the description of specialized (secondary) metabolites contained in the Ecuadorian flora, to contribute to the advance in its phytochemical and phytopharmaceutical knowledge [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. Within a project focused on the description of new essential oils (EOs) [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ], the aim of this study is to describe a novel chemical profile of an already known EO, distilled from the aerial parts of Clinopodium taxifolium (Kunth) Govaerts.…”
Section: Introductionmentioning
confidence: 99%
“…and Satureja lineata Epling. [ 10 , 21 , 22 , 23 ]. This plant is also known with the homonym Clinopodium taxifolium (Kunth) Harley [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation